2018
DOI: 10.1097/med.0000000000000404
|View full text |Cite
|
Sign up to set email alerts
|

Public health impact of androgens

Abstract: Recent studies have demonstrated marked adverse effects of long-term androgen abuse. As increasing numbers of androgen abusers reach middle age, these effects will likely represent an emerging public health problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
0
32
0
3
Order By: Relevance
“…The most reported long-term side effects affect the cardiovascular system, such as cardiomyopathy and atherosclerotic disease. Hypogonadism is a frequent finding in AAS abusers and need to be taken into consideration when AAS use is suspected in order to undertake aggressive treatment [ 8 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most reported long-term side effects affect the cardiovascular system, such as cardiomyopathy and atherosclerotic disease. Hypogonadism is a frequent finding in AAS abusers and need to be taken into consideration when AAS use is suspected in order to undertake aggressive treatment [ 8 , 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, AAS use is still very popular and 1–3% of US inhabitants have been estimated to be AAS users [ 6 ]. Moreover, in younger subjects’ higher estimates have been reported [ 7 , 8 ]. However, AASs have side effects involving all organs, tissues and body functions, especially long-term toxicity involving the cardiovascular system and the reproductive system, therefore, their abuse is considered a public health issue [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While AAS doping remains a concern for sport, both at elite and recreational levels [15–17], the wider societal impact is now apparent [4, 18, 19]. Although prevalence estimates of clandestine behaviours such as AAS are notoriously difficult, a growing body of evidence has indicated that while well established in North America, northern Europe and Australia, there are concerns across the globe [6, 19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, considering a parenteral dose of testosterone enanthate or cypionate of 150–200 mg every two week in men with hypogonadism [ 13 ], the aforementioned abus dose is 6 to 500 times higher than that recommended in testosterone replacement therapy. AAS abuse is widespread and extending, becoming an alarming public health issue [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of AAS excess is a consequence of their numerous side effects, including endocrine dysfunctions, alterations of the cardiovascular system, liver toxicity, behavioral changes and even psychiatric disorders, some of them with severe endpoints [ 10 , 12 , 14 , 15 , 16 , 17 ]. The negative effects on the cardiovascular function have classically been divided into four categories: thrombotic, atherogenic, vasospastic, and cardiomyocyte direct toxicity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%